(untitled) (Praxis Educativa, 2026)
This article presents research results that problematize the hegemony of scientific knowledge in the Natural Sciences curriculum for the first cycle of basic education in the Chilean school system. The methodology is qualitative and interpretive; the curricular foundations of the natural sciences subject in the first cycle of basic education were analyzed. The information was approached through thematic analysis. The main findings demonstrate the presence of scientism in the curricular discourse, which translates into the invisibility, denial, or omission of knowledge other than the hegemonic one. Furthermore, the existence of a structural epistemic injustice is confirmed, expressed in the exclusion of situated knowledge. Based on this, we argue that this exclusion contributes to reproducing a monocultural curricular logic, removed from the sociocultural reality of students who pursue their schooling in educational settings with social and cultural diversity. We conclude that it is necessary to move toward a critical review of the science curriculum that recognizes and integrates other knowledge systems, fostering relevant, inclusive, and culturally relevant educational processes.